Nutrition, Ethics and Cancer, “To name things wrongly is to add to the misfortune of the world” - Diana Cardenas; Bruno Raynard; François Blot (Clinical Nutrition Open Science, 2023)
Summary: Medical nutrition therapy is a full-fledged treatment such as antibiotics, antidiabetics or mechanical ventilation. Like any medical procedure, evidence-based medical nutrition therapy (from its indication and introduction, to the eventual interruption thereof) goes along with ethical dilemmas, especially in the most extreme situations such as old age, end of life or critical care. But more than any medical intervention or therapeutic act, nutrition and food carries specific sociological and anthropological representations, and, therefore, a heavy symbolic and emotional burden. For several reasons, cancer is at the intersection of all these dimensions: the disease and its treatments severely affect the nutritional status; end-of-life situations in oncology are still frequent, leading to thorny ethical dilemmas. The difficulties in withholding and withdrawing nutrition and food due to the symbolic and emotional burden as well as the social function are at the forefront of said dilemmas. If nutrition is still struggling to find its rightful place, isn't it also because it struggles to be well named?The aim of this article is to analyze the ethical dilemmas, thought a socio-anthropological approach, that arise when it comes to feeding the cancer patient and to reflect on how the human based right approach can support the decision-making process in nutrition. The summarized case of Delphine G. is exemplary of these questions and will serve as the common thread of this analysis.